All-solid-state planar on-chip supercapacitors based on reduced graphene oxide by liquid-air interfacial assembly. (4th July 2018) - Liu, Linjing; Wang, Xin; Zhang, Guangyu
ABSTRACT: All-solid-state planar on-chip supercapacitors (APCSs) was prepared based on reduced graphene oxide films obtained by liquid-air interfacial assembly method and hydroiodic acid treatment. The reduced graphene oxide films (495.44 S cm −1 ) have good surface morphologies, uniform thickness and a higher carbon to oxygen atomic ratio (C/O = 11.5) after hydroiodic acid treatment. The APCSs based on reduced graphene oxide delivered an area capacitance 69.57 μF cm −2 and a stack capacitance 2.34 F cm −3 . Moveover, they show an energy density of 324.23 μWh cm −3 and a power density of 1167.21 μW cm −3 . The demonstrated APCSs provide an important reference for the study of planar supercapacitors.